1986
DOI: 10.1002/1098-108x(198605)5:4<747::aid-eat2260050413>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The predictive validity of the Dutch Restrained Eating Scale

Abstract: The present study aims to determine the predictive validity of the 10‐item Dutch Restrained Eating Scale. The ultimate criterion of restrained eating is the degree to which an individual eats less than he or she actually would like to eat. Since a study on both actual food consumption and restriction of food intake is very complicated, if not impossible, the difference between actual and desired intake of energy was studied indirectly, that is, from estimates of deviations from the required energy intake. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
247
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 341 publications
(254 citation statements)
references
References 15 publications
5
247
1
1
Order By: Relevance
“…Specifically, the data in Figure 1 suggested that, although there 20 was no moderating effect of BMI on the relationship between label and consumption, obese 21 participants seemed to eat less in response to seeing either a high or low fat label compared 22 to no label. The data in Figure 2 suggested that weight-concerned participants of lowest SES 23 seemed to eat less in response to seeing either a high or low fat label compared to no label.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Specifically, the data in Figure 1 suggested that, although there 20 was no moderating effect of BMI on the relationship between label and consumption, obese 21 participants seemed to eat less in response to seeing either a high or low fat label compared 22 to no label. The data in Figure 2 suggested that weight-concerned participants of lowest SES 23 seemed to eat less in response to seeing either a high or low fat label compared to no label.…”
mentioning
confidence: 95%
“…There was no 3-way interaction of low fat label, SES and BMI. 18 Post hoc tests indicated that seeing either label was associated with significantly reduced 19 consumption as overweight increased and with significantly reduced consumption in weight- 20 concerned participants of lowest SES. 21 These results provide some support for previous research finding paradoxical effects of 22 nutritional labelling.…”
mentioning
confidence: 99%
See 3 more Smart Citations